Damage detection and characterization in C-glass and E-glass fibre-reinforced polymer due to low and high velocity impact events - Safri, Syafiqah Nur Azrie (2014)
This thesis presents low velocity impact testing and high velocity impact testing on fibreglass reinforced polymer. The materials used in this experiment are Type Cglass/ Epoxy 600 g/m² and Type E-glass/Epoxy 800 g/m². The ultimate objective of this research is to conduct an experimental investigation using low velocity impact testing and high velocity impact testing to detect and quantify impact damage for Glass Fibre Reinforced Polymer Type C-glass/Epoxy 600 g/m² and Type Eglass/Epoxy 800 g/m² plate. The purpose of this research is to choose the best material for structural application by comparing the mechanical properties and damage characteristics of GFRP Type C-glass/Epoxy 600 g/m² and Type Eglass/Epoxy 800 g/m². The experimental results of low-energy drop-weight impact tests on woven-roving Glass Fibre Reinforced Polymer (GFRP) type C-glass/Epoxy 600 g/m² and Type Eglass/ Epoxy 800 g/m² are presented. The effects of specimen thickness based on the number of plies and impact energy are investigated. Impact damage and response was observed for eight levels of impact energies, 6, 12, 18, 24, 30, 36, 42 and 48 J. From the experimental studies, it can be concluded that for each type of GFRP, the impact energy showed excellent correlation with the impact response. The difference in the number of plies fabricated and the mechanical properties for both types of GFRP do affect the impact response and impact damage of the specimens tested. The experimental results of the high velocity impact test using a Single Stage Gas Gun (SSGG) show that both types of GFRP exhibit damage in terms of fibre cracking, and fibre pull out after being tested with four different gas gun pressures. Before fibre failure occurs, they undergo matrix cracking and delamination processes first. As the gas gun pressure increases, the initial velocity of the projectile increases,the projectile kinetic energy increases, the maximum force exerted on the specimen increases, and the energy absorbed by the specimen also increases. Most of the impacted specimens show that GFRP type E-glass/Epoxy 800 g/m² experienced a smaller damage area compared to type C-glass/Epoxy 600 g/m². From the test, the effect of the shape of the projectile, the target thickness and the gas gun pressure affected the performance of GFRP. It can be concluded that GFRP type E-glass/Epoxy 800 g/m² is stronger compared to GFRP type C-glass/Epoxy 600 g/m² since it has more fibre volume since it is higher in density and has good mechanical properties. Therefore, GFRP type E-glass/Epoxy 800 g/m² is recommended to be used in structural applications.